CD4+T cells in ageing-associated interstitial lung abnormalities show evidence of pro-inflammatory phenotypic and functional profile. Issue 2 (9th December 2020) - Machahua, Carlos; Buendia-Roldan, Ivette; Ocaña-Guzman, Ranferi; Molina-Molina, María; Pardo, Annie; Chavez-Galan, Leslie; Selman, Moises
Abstract : Background: Interstitial lung abnormalities (ILA) occur in around 10% of subjects over 60 years, and are associated with a higher rate of all-cause mortality. The pathogenic mechanisms are unclear, and the putative contribution of alterations in the immune response has not been explored. Normal ageing is associated with immune deficiencies, including Naïve T-cell decrease and greater expression of the proliferative-limiting, co-inhibitory receptor killer-cell lectin-like receptor G1 (KLRG1). Objective: To evaluate the frequency and activation state of different T-cell subpopulations in ILA subjects. Methods: Peripheral blood mononuclear cells were obtained from 15 individuals with ILA, 21 age-matched controls and 28 healthy young subjects. T-cells phenotype was characterised by flow cytometry, and proliferation and activation by stimulation with anti-CD3/anti-CD28 or phorbol myristate acetate/ionomycin; KLRG1 isoforms were evaluated by western blot and cytokines were quantified by ELISA and Multiplex. Results: A significant increase of Naïve CD4+T cells together with a decrease of central and effector memory CD4+T cells was observed in ILA compared with age-matched controls. CD4+T cells from ILA subjects exhibited greater basal proliferation, which raised after anti-CD3/anti-CD28 stimulation. Additionally, a significant increase in the levels of interleukin-6 and interferon gamma was observed in isolated CD4+T cells and plasma of ILA subjects. They also displayed fewer KLRG1+/CD4+T cells with an increase of circulating E-cadherin, the ligand of KLRG1+. No changes were observed with CD8+T cell subsets. Conclusion: CD4+T cells from ILA subjects are highly proliferative and show an excessive functional activity, likely related to the loss of KLRG1 expression, which may contribute to an inflammatory state and the development of ILA.